Parameter controlled instance generation for lot sizing problems - Alf Kimms (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1996)
This contribution defines an instance generator for capacitated, dynamic, multi-level lot sizing problems. It provides sophisticated methods for generating systematically varied parameter level combinations automatically. This helps to perform evaluations of lot sizing methods according to a factorial experimental design and to establish Standard test-beds.
Keywords: 650; Instance generator; experimental design; lot sizing